Representações das práticas de leitura de normalistas do Instituto de Educação Rui Barbosa durante as décadas de 60 e 70 do século XX - Melo, Sônia Pinto de Albuquerque (2009)
The proposal of this study is to investigate the representations of practical of reading of normalistas of the Institute of Education Rui Barbosa IERB, in the decades of 60 and 70 of century XX. The theoretician-metodológicos associates itself to it estimated of History of the Feminine Education and of Cultural History under the perspective of History of the Reading. The used principal sources had been depositions of the formerones of the investigated period, the note passbooks of professors of Literature and Portuguese Language of the decades of 60 and 70 of century XX, beyond fotonovelas and clandestine romances read for the normalistas, in order to know and to understand the appropriations of such practical in the process of formation of these readers, considering itself that the reading experiences in the acquisition of habitus, as well as they give indications of the behavior, of the values and of the acquired experiences.